TINDAK TUTUR DIREKTIF DALAM NOVEL JILBAB TRAVELER LOVE SPARKS IN KOREA KARYA ASMA NADIA - Erina Ponita; Auzar Auzar; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to describe the form and function of directive speech acts in novel Jilbab Traveler Love Sparks in Korea by Asma Nadia. This research is descriptive qualitative research. To collect the data, the researcher used documentation techniques. Based on the data analysis that has been done, the researcher found 244 data with sub-divisions (a)requestives 41 data and divided into several functions such as: requesting function 17 data, bagged function 1 data, praying function 3 data, inviting function 6 data, hopping function 13 data, and invite and hope function 1 data. (b) questions 69 data and serve as asking, (c) requirement 45 data and divided into several function such as: commanding function 7 data, demanding function 12 data, directing function 4 data, requiring function 18 data, requirement function 3 data, and setting function 1 data. (d) prohibitives 9 data and divided into several function such as: prohibit function 8 data and limiting function 1 data. (e) permissives 6 data and divided into several function such as: approving function 5 data and allowing function 1 data. (f) advisories 54 data and divided into several function such as: advising function 7 data, reminding function 24 data, and recommending function 23 data.Keywords: Speech act, directive speech act, novel